2014
DOI: 10.1371/journal.pone.0114350
|View full text |Cite|
|
Sign up to set email alerts
|

Fears and Beliefs in Rheumatoid Arthritis and Spondyloarthritis: A Qualitative Study

Abstract: ObjectivesTo explore beliefs and apprehensions about disease and its treatment in patients with rheumatoid arthritis and spondyloarthritis.Methods25 patients with rheumatoid arthritis and 25 with spondyloarthritis participated in semi-structured interviews about their disease and its treatment. The interviews were performed by trained interviewers in participants' homes. The interviews were recorded and the main themes identified by content analysis.ResultsPatients differentiated between the underlying cause o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 26 publications
3
51
0
1
Order By: Relevance
“…Use of a threshold lower than 7 would clearly generate higher percentages of “believers”. Finally, it is important to note that the items of the QuAD were derived from a qualitative survey of French patients [ 11 ]. It is possible that patients in other countries or cultures would have different concerns [ 27 , 28 ], which would be interesting to evaluate in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of a threshold lower than 7 would clearly generate higher percentages of “believers”. Finally, it is important to note that the items of the QuAD were derived from a qualitative survey of French patients [ 11 ]. It is possible that patients in other countries or cultures would have different concerns [ 27 , 28 ], which would be interesting to evaluate in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…A previous qualitative study of disease perception in patients with RA or axSpA was performed in 50 patients (25 with RA and 25 with axSpA) [ 11 ]. Based on data from this study [ 11 ], all items reported by > 5% of patients were rephrased as assertions, with help from a partnering patient organization. This questionnaire covered the most widely held perceptions about disease and treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Further studies allowing comparison of fear and beliefs of patients in different stages of RA is necessary since it has been shown that beliefs about the consequences of disease and expectations of patients varied according to the stage of RA and familiarity with other people with the same clinical condition [13,18].…”
Section: Discussionmentioning
confidence: 99%
“…Fear of disease progression and disability was the second most described category (N = 9/32 articles reporting fears, 28.1%) ( Table 2); Fears related to pregnancy and parenting roles were reported in three articles (9.4% of the 32 articles reporting fears) ( Table 2). Patients who participated in these articles were recruited in Europe and reported the fear of drugs causing birth defects, fear of genetic transfer, fear of being unable to fulfill parenting roles, fear of not being able to prevent accidents and fear of dropping a small baby or toddler [17][18][19].…”
Section: Fearsmentioning
confidence: 99%
See 1 more Smart Citation